Epigenetic variation creates potential for evolution of plant phenotypic plasticity. Issue 1 (1st November 2012) - Zhang, Yuan‐Ye; Fischer, Markus; Colot, Vincent; Bossdorf, Oliver
Summary: Heritable variation in plant phenotypes, and thus potential for evolutionary change, can in principle not only be caused by variation in DNA sequence, but also by underlying epigenetic variation. However, the potential scope of such phenotypic effects and their evolutionary significance are largely unexplored. Here, we conducted a glasshouse experiment in which we tested the response of a large number of epigenetic recombinant inbred lines (epiRILs) of Arabidopsis thaliana – lines that are nearly isogenic but highly variable at the level of DNA methylation – to drought and increased nutrient conditions. We found significant heritable variation among epiRILs both in the means of several ecologically important plant traits and in their plasticities to drought and nutrients. Significant selection gradients, that is, fitness correlations, of several mean traits and plasticities suggest that selection could act on this epigenetically based phenotypic variation. Our study provides evidence that variation in DNA methylation can cause substantial heritable variation of ecologically important plant traits, including root allocation, drought tolerance and nutrient plasticity, and that rapid evolution based on epigenetic variation alone should thus be possible.